Genetic modification of survival in tissue-specific knockout mice with mitochondrial cardiomyopathy - Li, Hong (The National Academy of Sciences, 2000)
We recently described a mouse model that reproduces important pathophysiological features of mitochondrial DNA (mtDNA) mutation diseases. The gene for mouse mitochondrial transcription factor A, Tfam (also called mtTFA), a nucleus-encoded key regulator of mtDNA expression, was targeted with loxP sites (Tfam(loxP)) and disrupted in vivo by transgenic expression of cre-recombinase from the muscle creatinine kinase (Ckmm) promoter. This promoter is active from embryonic day 13, and the knockouts had normal respiratory chain function in the heart at birth and developed mitochondrial cardiomyopathy postnatally. In this paper, we describe a heart-knockout strain obtained by mating Tfam(loxP) mice to animals expressing cre-recombinase from the α-myosin heavy chain (Myhca) promoter. This promoter is active from embryonic day 8, and the knockouts had onset of mitochondrial cardiomyopathy during embryogenesis. The age of onset of cardiac respiratory chain dysfunction can thus be controlled by temporal regulation of cre-recombinase expression. Further characterization demonstrated that ≈75% of the knockouts died in the neonatal period, whereas, surprisingly, ≈25% survived for several months before dying from dilated cardiomyopathy with atrioventricular heart conduction blocks. Modifying gene(s) affect the life span of the knockouts, because ≈95% of the knockout offspring from an intercross of the longer-living knockouts survived the neonatal period. Thus, the tissue-specific knockouts we describe here not only reproduce important pathophysiological features of mitochondrial cardiomyopathy but also provide a powerful system by which to identify modifying genes of potential therapeutic value.